PENINGKATAN KETERAMPILAN INTERAKSI SOSIAL ANAK MELALUI PERMAINAN ULAR TANGGA EDUKASI DI TAMAN KANAK-KANAK YAPIGUNA GUGUAK KABUPATEN LIMA PULUH KOTA - Sri Indria Yunyul; Indra Yeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This classroom action research aimed to improve children’s social interaction skills through educational snakes and ladders games at TK Yapiguna Guguak, Lima Puluh Kota Regency. The study used the Kemmis and McTaggart classroom action research model consisting of planning, acting, observing, and reflecting stages conducted in two cycles. The subjects were 15 children aged 5–6 years. Data collection techniques included observation, field notes, documentation, and child development assessment sheets. The results showed an increase in children’s social interaction skills in every cycle. In the pre-action stage, only 33% of children achieved the criteria of Developing as Expected (BSH) and Very Well Developed (BSB). In Cycle I, the percentage increased to 60%, and in Cycle II it reached 86%. The improvement was seen in communication, cooperation, empathy, and social adaptation aspects. Educational snakes and ladders games provided opportunities for children to communicate, cooperate, wait for turns, obey rules, and build positive social relationships. Therefore, educational snakes and ladders games can be used as an effective and innovative learning method to improve early childhood social interaction skills.